Nous sommes tous devant le même écran : Merleau-Ponty et l’expérience cinématographique - Calabretto, Maria (Scenari, 2024)
In phenomenological aesthetics, the experience unfolded by the work of art has always been a space for achieving a suspension of our ordinary experience. From this position, we wonder whether we can apply the same power to cinematographic art. Thanks to the various techniques employed by the seventh art, it can inaugurate a particularly successful experience of epoché. Merleau-Ponty succeeds in capturing this potential, interweaving his philosophical project with the event that cinema reveals. It is the possibility, on the one hand, of living a shared experience, and on the other, of immersing ourselves in another experience, taking us out of an exclusively subjective dimension. The analysis of Bresson’s film, Au hasard Balthazar, will help us understand the cinematic vision of the French phenomenologist, who finds in the cinematic medium a veritable interlocutor for his philosophy.